Cashew Nut Shell Liquid : A Goldfield for Functional Materials - Anilkumar, Parambath (Springer International Publishing : Imprint: Springer, 2017)
This book highlights and reviews the renewable feed stock principle of green nanotechnology by focusing the use of plant-derived cardanol as a renewable starting material for the synthesis of advanced materials. The book presents the chemistry of cardanol and methods of isolation, covers macro and nano structures based on cardanol as well as potential applications of such materials. Future perspectives on cardanol based green nanotechnology are highlighted in the final chapter.
Keywords: Materials science.; Renewable energy resources.; Nanochemistry.; Renewable energy sources.; Alternate energy sources.; Green energy industries.; Nanotechnology.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books